PEMANFAATAN LIMBAH KOTORAN TERNAK SEBAGAI BIOGAS YANG RAMAH LINGKUNGAN DAN BERKELANJUTAN - Septiani Mangiwa (JURNAL PENGABDIAN PAPUA, 2017)
The need for fuel continues to increase along with population growth and development of the times. But what happens when this is fossil fuel supplies continue to decline. Therefore, it is necessary to find an alternative that can provide renewable fuels and environmentally friendly. One form of alternative energy that has the prospective to be developed is biogas. Biogas can be obtained by making use of livestock manure. Moreover, in the manufacture of biogas, also produced fertilizer which can be used for plant fertility. Do counseling / guidance and knowledge transfer to the public to utilize the manure waste as biogas instead of wood fuel / kerosene and manure that are environmentally friendly and provide an example to the community about how to make a tool of sewage treatment of livestock manure into biogas as appropriate technology affordable by the public as a form of community service. This event was held for groups of pig farmers in Konya, Village Hedam, Heram District Jayapura City in the form of counseling / guidance and training to the community by using the method of lecture, discussion, question and answer, demonstration and practice of waste processing pig manure into biogas. Keywords: Biogas, fossil, fuel, environment, wood fuel